Effectiveness Analysis of Granulator Machine Using OEE and FTA at NPK Phonska I PT Petrokimia Gresik - Hendrawan, Mochammad Ega; Jufriyanto, Mohammad (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study aims to evaluate and improve the effectiveness of the granulator machine at the NPK Phonska I Plant of PT Petrokimia Gresik through an integrated Overall Equipment Effectiveness (OEE) and Fault Tree Analysis (FTA) approach. The granulator machine frequently fails to achieve the 2024 production target of 37,500 tons per month due to high downtime (89.24 hours/month) and defective products reaching 17,847 tons annually. The research applies OEE to calculate availability, performance efficiency, and quality rate, followed by Six Big Losses classification and FTA to determine the fundamental causes of machine underperformance. The findings show that the average OEE is 62.1%, significantly below the world-class benchmark of 85%, with the largest losses coming from equipment failure (49.00%) and reduced speed losses (37.75%). The novelty of this research lies in the integration of OEE–FTA with additional correlation analysis between downtime and defect ratios and the identification of heat-related and material-variability effects specific to fertilizer granulation. Scientifically, this study contributes a structured improvement framework tailored for the national fertilizer industry, offering evidence-based maintenance strategies and operational insights to support the company’s effort in achieving world-class machine effectiveness.